1965
DOI: 10.1113/jphysiol.1965.sp007574
|View full text |Cite
|
Sign up to set email alerts
|

Influence of osmotic strength on cross‐section and volume of isolated single muscle fibres

Abstract: Despite long-continued interest in the subject, uncertainty still exists about some fundamental aspects of the osmotic behaviour of striated muscle cells. One unsettled problem has to do with the extent to which the fibre adjusts its volume in response to changes in the osmotic pressure of the bathing medium. There is abundant evidence, both from indirect observations and from direct measurements of volume, that under conditions in which one might expect the transfer of solutes across the cell membrane to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
220
4

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(255 citation statements)
references
References 7 publications
31
220
4
Order By: Relevance
“…Here we show that detubulation of MHN and MHS swine fibers induces a small increase in [Ca 2ϩ ] r in both types of muscle fibers (16% MHN and 10% MHS, respectively). This increment may be related to the change in muscle volume, water moving out the cell, upon exposure to hypertonic solution, because striated muscle behaves as a perfect osmometer, decreasing its volume in proportion to the tonicity of the bathing medium (53,54). The increase in [Ca 2ϩ ] r provoked by Na ϩ -free solution after muscle detubulation is reduced by 62% in MHN and 68% in MHS compared in non-detubulated muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that detubulation of MHN and MHS swine fibers induces a small increase in [Ca 2ϩ ] r in both types of muscle fibers (16% MHN and 10% MHS, respectively). This increment may be related to the change in muscle volume, water moving out the cell, upon exposure to hypertonic solution, because striated muscle behaves as a perfect osmometer, decreasing its volume in proportion to the tonicity of the bathing medium (53,54). The increase in [Ca 2ϩ ] r provoked by Na ϩ -free solution after muscle detubulation is reduced by 62% in MHN and 68% in MHS compared in non-detubulated muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…These include administrations of tetracaine, dantrolene Na, Ca 2+ deprivation, and nifedipine (Putney and Bianchi, 1974;Huang, 1981aHuang, , 1990Huang, , 1991Hui, 1983;Bruin, Fitts, Pizarro, and Rios, 1988;Rios and Brum, 1987). The physiological effects of changes in extracellular tonicity have been attributed to changes in intracellular ionic strength arising from the consequent fiber volume change (Howarth, 1958;Dydynska and Wilkie, 1963;Blinks, 1965;Caputo, 1968;Gordon and Godt, 1970). The mechanism for their influence on charge may therefore differ from those of the pharmacological agents.…”
Section: Discussionmentioning
confidence: 99%
“…One source of error arose from the fact that muscle fibres are rarely circular in cross-section. Blinks (1965) compared the average value of actual cross-sectional area with the estimated areas based on (1) the circular, or (2) elliptical assumption (Gordon, Huxley & Julian, 1966). His result showed that on the circular assumption the estimated area was 121 %, and on the elliptical assumption 104 % of the actual area.…”
Section: Methodsmentioning
confidence: 99%
“…2A, B). pressure (Dydynska & Wilkie, 1963;Reuben, Lopez, Brandt & Grundfest, 1963;Blinks, 1965), G, ought to increase with osmotic pressure. An increase of myoplasmic viscosity might be responsible for this unexpected reduction of Gi.…”
Section: Isolated Fibres (A) Determination Of G1 Gm and CMmentioning
confidence: 99%